(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This paper reflects on some linguistic constraints in the etymological analysis of personal names of Western Hispania. To be exact, any of the anthroponimical roots referring to numerals (tritio-, turio-, pentio-) cannot be assigned to a specific Indo-European family. And provided that it is the geographical distribution what helps to place them from a linguistic point of view, we propose that Linguistics should make the most of the importance of the Linguistic Geography, based on the coherent repetition of series of elements, in order to analyze the ancient material of Roman Hispania.